Different Estimation Methods for System Reliability Multi-Components model: Exponentiated Weibull Distribution - Salman, Abbas Najim; Sail, Fatima Hadi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In this paper, estimation of system reliability of the multi-components in stress-strength model R(s,k) is considered, when the stress and strength are independent random variables and follows the Exponentiated Weibull Distribution (EWD) with known first shape parameter Î¸ and, the second shape parameter Î± is unknown using different estimation methods. Comparisons among the proposed estimators through  Monte Carlo simulation technique were made depend on mean squared error (MSE)  criteria